Ovicidal effect of the essential oils from 18 Brazilian Piper species: controlling Anticarsia gemmatalis (Lepidoptera, Erebidae) at the initial stage of development - Diones Krinski; Luís Amilton Foerster; Cicero Deschamps (Acta Scientiarum. Agronomy, 2018)
The toxicities of essential oils (EOs) from 18 species of Brazilian Piperaceae were assessed on eggs of the velvetbean caterpillar, Anticarsia gemmatalis. Oils were extracted using steam distillation, and dilutions were made for bioassays at concentrations of 0.25, 0.5, 1.0, 2.0, and 4.0%. All EOs reduced larval hatching. The lowest lethal concentrations were obtained from Piper fuligineum (SP), Piper mollicomum “chemotype 1” (SP), Piper mosenii (PR), Piper aduncum (PA) and Piper marginatum (PA). Ovicidal activity is related to the potential toxicity of several compounds, especially dilapiolle, myristicin, asaricine, spathulenol and piperitone. According to our results, EOs from 16 Brazilian Piper species have potential for use as biorational botanical insecticides.